Application of the Improved Clustering Algorithm in Operating Room Nursing Recommendation under the Background of Medical Big Data. (23rd March 2022) - Wu, Xiaofang; Wang, Chunjun; Cai, Fangzhen; Wu, Yingfen
Abstract : The nursing work in the operating room has the characteristics of long time, strong technicality, and heavy work, which have an important influence on the quality of the operation. Operating room nursing recommendations based on data mining technology can solve a series of practical problems in clinical nursing and nursing management. This paper selects the clustering algorithm in commonly used data mining technology as the research object and actually analyzes the impact of this algorithm in operating room nursing recommendations. At this stage, there is little research on data mining technology in the field of nursing in China. This paper aims to provide new ideas for the field of nursing research by exploring the actual application in the field of nursing.